Barbarian phenomena and their impact on the evolution National activity in the Far Maghreb 1930-1937 (Journal of the College of Basic Education, 2022)
That the barbaric policy is the last thing that French colonialism guided to eliminate the elements of Morocco and integrate it with France. These immigrants have privileges at the expense of the people of Al-Aqsa Morocco, but this immigration policy did not pay off, or all of it.